Traditional Law of The Nusantara; Reflection of The Indigenous Justice System in Indonesia - Sukendar Sukendar (LEGAL BRIEF, 2021)
The development of the order of life in Indonesia, has always experienced very significant changes and developments, these developments have begun to occur when this country was not yet independent, one aspect that would like to be further improved in order to form a national judicial law is the customary justice system. This study uses a descriptive method with a qualitative approach and data triangulation analysis, the results of the study explain that the customary justice system is a system formed from various Indonesian values and culture, customary law by law is not yet included in a written law but its existence is still maintained Until now, customary law is reflected as a characteristic of the nation because it is able to explore various values contained in society, such as the values of togetherness, mutual cooperation, having a high national spirit, and upholding the sense of unity and integrity of the Republic of Indonesia. k Indonesia, besides that, there are many who think that customary law is the original personality and nature of the Indonesian nation that cannot be left behind and must be enforced for the sake of various interests of the ideals of the Indonesian nation and state.